Using behaviour change and implementation science to address low referral rates in oncology - Janet C. Long; Deborah Debono; Rachel Williams; Elizabeth Salisbury; Sharron O’Neill; Elizabeth Eykman; Jordan Butler; Robert Rawson; Kim-Chi Phan-Thien; Stephen R. Thompson; Jeffrey Braithwaite; Melvin Chin; et al. (BMC Health Services Research, 2018)
Abstract Background Patients undergoing surgery for bowel cancer now have a routine screening test to assess their genetic predisposition to this and other cancers (Lynch syndrome). A result indicating a high risk should trigger referral to a genetic clinic for diagnostic testing, information, and management. Appropriate management of Lynch syndrome lowers morbidity and mortality from cancer for patients and their family, but referral rates are low. The aim of this project was to increase referral rates for patients at high risk of Lynch syndrome at two Australian hospitals, using the Theoretical Domains Framework (TDF) Implementation approach. Methods Multidisciplinary teams at each hospital mapped the referral process and discussed barriers to referral. A 12-month retrospective audit measured baseline referral rates. The validated Influences on Patient Safety Behaviours Questionnaire was administered to evaluate barriers using the TDF. Results were discussed in focus groups and interviews, and interventions co-designed, guided by theory. Continuous monitoring audits assessed change in referral rates. Results Teams (n = 8, 11) at each hospital mapped referral processes. Baseline referral rates were 80% (4/5) from 71 screened patients and 8% (1/14) from 113 patients respectively. The questionnaire response rate was 51% (36/71). Most significant barrier domains were: ‘environmental context;’ ‘memory and decision making;’ ‘skills;’ and ‘beliefs about capabilities.’ Focus groups and interviews with 19 healthcare professionals confirmed these domains as significant. Fifteen interventions were proposed considering both emerging and theory-based results. Interventions included: clarification of pathology reports, education, introduction of e-referrals, and inclusion of genetic status in documentation. Audits continued to December 2016 showing a change in pathology processes which increased the accuracy of screening. The referral rate remained low: 46% at Hospital A and 9% Hospital B. Results suggest patients who have their referral deferred for some reason are not referred later. Conclusion Lynch syndrome is typical of low incidence problems likely to overwhelm the system as genomic testing becomes mainstream. It is crucial for health researchers to test methods and define generalizable solutions to address this problem. Whilst our approach did not improve referrals, we have deepened our understanding of barriers to referral and approaches to low frequency conditions.